Overactivation of the complement system may be involved in intrarenal arteriolar lesions in IgA nephropathy - Guo, Wei-yi; An, Xiu-ping; Sun, Li-jun; Dong, Hong-rui; Cheng, Wen-rong; Ye, Nan; Wang, Guo-qin; Xu, Xiao-yi; Zhao, Zhi-rui; Cheng, Hong (Frontiers in Medicine, 2022)
Introduction: IgA nephropathy (IgAN) encompasses a wide range of clinical and histology features. Some patients present without hematuria, with or without hypertension, still rapidly progress in renal function. Renal pathology of this part of patients were predominant intrarenal arteriolar lesions, rarely presented glomerular proliferative lesions. We aim to investigate the clinical and pathological characteristics and prognosis of these IgAN patients and initially explore whether the abnormal activation of complement is involved in the intrarenal arteriolar lesions of IgAN. Methods: 866 patients with renal biopsy-proven IgAN diagnosed at Beijing Anzhen Hospital were recruited. IgAN patients without intrarenal arteriolar lesions and proliferative lesions were excluded (n=115), the rest were divided into arteriolar lesions group (n=202) and proliferative lesions group (n=549). Among them, 255 patients were regularly followed up for at least 1 year. Renal biopsy tissues of 104 IgAN patients were stained for complement components by immunohistochemistry and immunofluorescence. Results: Compared with proliferative lesions group, the arteriolar lesions group experienced high percentage of hypertension (p=0.004), low percentage of gross hematuria (p=0.001), microscopic hematuria (p<0.001) and less initial proteinuria (p=0.033). Renal survival between the two groups was not significantly different (p=0.133). MBL, C4d, FH and FHR5, C3c and MAC deposited on intrarenal arteriole in arteriolar lesions group. Compare with the proliferative lesion group, the arteriolar lesions group exhibited a higher intensity of C3c deposition on the intrarenal arterioles (p=0.048). C3c and CD31 co-deposited on intrarenal arterioles area in patients with intrarenal arteriolar lesions. Conclusions: Renal survival of the IgAN patients in arteriolar lesions group was not better than those in proliferative lesions group. Abnormal activation of complement may be involved in the pathogenesis of arteriolar damage through the injury of endothelial cells in this clinical phenotype of IgAN.